Estimation of the Prevalence of Inadequate and Excessive Iodine Intakes in School-Age Children from the Adjusted Distribution of Urinary Iodine Concentrations from Population Surveys. Issue 6 (4th May 2016) - Zimmermann, Michael B; Hussein, Izzeldin; Al Ghannami, Samia; El Badawi, Salah; Al Hamad, Nawal M; Abbas Hajj, Basima; Al-Thani, Mohamed; Al-Thani, Al Anoud; Winichagoon, Pattanee; Pongcharoen, Tippawan; van der Haar, Frits; Qing-Zhen, Jia; et al.
Abstract: Background: The urinary iodine concentration (UIC), a biomarker of iodine intake, is used to assess population iodine status by deriving the median UIC, but this does not quantify the percentage of individuals with habitually deficient or excess iodine intakes. Individuals with a UIC <100 μg/L or ≥300 μg/L are often incorrectly classified as having deficient or excess intakes, but this likely overestimates the true prevalence. Objective: Our aim was to estimate the prevalence of inadequate and excess iodine intake in children (aged 4–14 y) with the distribution of spot UIC from iodine surveys. Methods: With the use of data from national iodine studies (Kuwait, Oman, Thailand, and Qatar) and a regional study (China) in children ( n = 6117) in which a repeat UIC was obtained in a subsample ( n = 1060), we calculated daily iodine intake from spot UICs from the relation between body weight and 24-h urine volume and within-person variation by using the repeat UIC. We also estimated pooled external within-person proportion of total variances by region. We used within-person variance proportions to obtain the prevalence of inadequate or excess usual iodine intake by using the Estimated Average Requirement (EAR)/Tolerable Upper Intake Level (UL) cutoff method. Results: Median UICs in Kuwait, Oman, China, Thailand, and Qatar were 132, 192, 199, 262, and 333 μg/L, respectively. Internal within-person variance proportions ranged from 25.0% to 80.0%, and pooled regional external estimates ranged from 40.4% to 77.5%. The prevalence of inadequate and excess intakes as defined by the adjusted EAR/UL cutoff method was ∼45–99% lower than those defined by a spot UIC <100 μg/L or ≥300 μg/L ( P < 0.01). Conclusions: Applying the EAR/UL cutoff method to iodine intakes from adjusted UIC distributions is a promising approach to estimate the number of individuals with deficient or excess iodine intakes.